se a soma das raízes da equação x ao quadrado -2 m x + m = 0 e 4 então então produto delas é:
a) 4
b) 3
c) 16
d) 2
e) 1
Soluções para a tarefa
Respondido por
1
a= 1
b = -2m
c = m
Bhaskara
![x_{1}+ x_{2}= \frac{2m+ \sqrt{4 m^{2}-4m } }{2} + \frac{2m- \sqrt{4 m^{2}-4m } }{2} x_{1}+ x_{2}= \frac{2m+ \sqrt{4 m^{2}-4m } }{2} + \frac{2m- \sqrt{4 m^{2}-4m } }{2}](https://tex.z-dn.net/?f=+x_%7B1%7D%2B+x_%7B2%7D%3D+++%5Cfrac%7B2m%2B+%5Csqrt%7B4+m%5E%7B2%7D-4m+%7D+%7D%7B2%7D+%2B+%5Cfrac%7B2m-+%5Csqrt%7B4+m%5E%7B2%7D-4m+%7D+%7D%7B2%7D+)
m + m = 4 ⇒ m = 2
a = 1
b= -4
c = 2
![x_{1}. x_{2}= \frac{4+ \sqrt{4.4-8} }{2}. \frac{4- \sqrt{4.4-8} }{2} = (2+ \sqrt{8}).(2- \sqrt{8)}=4-8=-4 x_{1}. x_{2}= \frac{4+ \sqrt{4.4-8} }{2}. \frac{4- \sqrt{4.4-8} }{2} = (2+ \sqrt{8}).(2- \sqrt{8)}=4-8=-4](https://tex.z-dn.net/?f=+x_%7B1%7D.+x_%7B2%7D%3D+%5Cfrac%7B4%2B+%5Csqrt%7B4.4-8%7D+%7D%7B2%7D.+%5Cfrac%7B4-+%5Csqrt%7B4.4-8%7D+%7D%7B2%7D+%3D+%282%2B+%5Csqrt%7B8%7D%29.%282-+%5Csqrt%7B8%29%7D%3D4-8%3D-4++)
Letra A
b = -2m
c = m
Bhaskara
m + m = 4 ⇒ m = 2
a = 1
b= -4
c = 2
Letra A
Perguntas interessantes
História,
11 meses atrás
História,
11 meses atrás
Ed. Física,
11 meses atrás
Sociologia,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás